Globalization and social change : people and places in a divided world - Perrons, Diane (Routledge, 2004)
Globalization and Social Change has a refreshing new perspective on globalization and widening social and spatial inequalities. The book combines original argument with a clear exposition of the underlying processes and is illustrated through a.